HUBUNGAN LAMA ROTASI KERJA DENGAN KINERJA PERAWAT DALAM PELAKSANAAN ASUHAN KEPERAWATAN DI RUMAH SAKIT BINA SEHAT JEMBER - Said Mardjanto; Irwin Santoni (Jurnal Kesehatan dr. Soebandi, 2016)
Being in a room with a long time will lead to work boredom in nurses that can have an impact on performance degradation. Work rotation is carried out by the hospital management to reduce work boredom so that it can motivate nurses to show better performance. Nurse performance can be seen from how the implementation of nursing care. The success of service at the Hospital is influenced by nurse performance. The purpose of this study is to know the relationship between work rotation length and the performance of nurses in the implementation of nursing care at the Bina Sehat Hospital in Jember held in May 2014. This research data is presented in a quantitative form using a correlational research design with a cross sectional approach. The number of research samples as many as 45 nurses. The sampling technique uses simple random sampling. Data collection uses questionnaires and observation sheets. Data is analyzed using the Spearman Rank Rank Correlation Coefficient Test. The results of this study were obtained P value 0.003 or P Value <0.05, this correlation was seen from the 3% error rate or 97% significance level. Great correlation or Spearman Rank correlation value 0.431 or 43.1% shows a positive correlation with sufficient correlation strength. The conclusion of this study is the longer the rotation time of work, the better the performance of nurses in the implementation of nursing care. Further research can use other variables that also affect the performance of nurses in addition to being seen from nursing care such as responsiveness, discipline, and workload